Peningkatan Aspek Integritas dan Aspek Teknologi Bagi Civitas Akademika Hukum Guna Mewujudkan Profesionalisme Hukum dan Cakap Literasi Digital: Improving Integrity Aspects and Technological Aspects for the Legal Academic Community to Realize Legal Professionalism and Digital Literacy - Hidayatulloh, Syarif; Wulandhani, Feni (Fakultas Hukum Universitas Negeri Semarang, 2021)
Integrity and technology aspects are very much needed in the current era in increasing legal professionalism and digital literacy skills. The legal academic community has an important role in the development of aspects of integrity and development of technological aspects. This is related to the realization of the process and results of the legal profession that can be highly competitive and make a positive contribution to the realization of a just law. The issues that will be studied and analyzed in this research are: first, improving the integrity and technological aspects for the legal academic community. Second, the influence of an attitude of integrity and technology proficiency in order to realize legal professionalism and digital literacy skills. The research method used in this paper is normative legal research with a concept approach, legislation and case approach. This study aims to determine the integrity and technological aspects for the legal academic community. In addition, to determine the influence of integrity and technology skills in order to realize legal professionalism and digital literacy skills. The results of this study conclude that: first, improving the integrity and technological aspects is very necessary for the legal academic community. This is related to the process and results for legal profession actors in their integrity and in adapting technology to make a positive contribution to the realization of a just legal climate. Second, there is the influence of an attitude of integrity and technological competence in order to realize legal professionalism and digital literacy skills. This is very influential on the realization of legal professionalism and skills in digital literacy.